How do I save cell therapy product's storage space?. Issue 4 (25th February 2023) - Kim, Grace H.; Patel, Nita; Reich‐Slotky, Ronit
Abstract: Background: Availability of liquid nitrogen (LN2) freezer storage space is a major challenge for many transplant programs as they continue to grow and accumulate products. The recent trend of allogeneic grafts cryopreservation that started during the COVID‐19 pandemic, made the situation even worse requiring an increase in storage capacity. Multi‐compartment cryopreservation bags can help save storage space but can be tricky to use. Here, we describe the validation of muti‐compartment cryopreservation bags for the purpose of donor lymphocyte infusion (DLI) aliquots. Methods: We validated the use of five compartment cryobags for cryopreservation of cell therapy products. Four products were cryopreserved using these bags and each compartment was tested post‐thaw for product volume distribution, total cell count recovery, and viability. Additionally, the integrity of both bag compartments and labels was assessed as well. Results: All tested specimens met post‐thaw viability and TNC recovery acceptability criteria. Fill volume was optimized at 24–25 mL for acceptable volume distribution between aliquots. With proper heat sealing between compartments, all aliquots retain their integrity and cryopreservation labels were adherent and legible. Conclusions: Muti‐compartment bags can be used successfully for cryopreservation of cell therapy products and increase storage capacity.